Youth violence in Metropolitan Lima - Velásquez Centeno, Carlos (1999)
Comparative-descriptive investigation guided to identify the existence of differences in the perception of the violence between the groups of students that have participated against the group of students that have not participated in violent acts in Metropolitan Lima. It was elaborated and is obtained the validity and reliability of the Scale of Perception of the Juvenile Violence, which presents three sub-scales: Self-justification, Perception of the Parental Control and Sociopatic Trends. It was applied to an intentional sample of 1132 pupils of National Educational Centers of 30 to the 50 year, of high school of the different canes of the city. The results found permit to determine that the group of participation in violent acts has an agreed perception with their condition, being expressed in the self-justification of their acts and their tendency to develop sociopatic conducts. In the same way the parents of the group of participation have a greater control over their children, that those of not-participation. The males of the group of participation are found more involved in violent acts that the women, in comparison with those of non-participation.